(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the efficiency of T. harzianum (Ecotrich®) and P. lilacinum (Nemat®) in the management of Pratylenchus brachyurus in soybean. The experimental design was randomized in blocks with four replications, consisting of six treatments, which consist of the control (1), an Avicta Completo® treatment (2), treatment with Nemat® (3), treatment with Avicta Complete® associated with Nemat® ( 4), a treatment with the association of Nenat® and Ecotrich® (5) and a treatment with the association of the bioinsecticides Ecotrich® and Nemat® and Avicta Completo® (6). The plots were composed of 7 lines with 0.45m line spacing, with a size of 3.60 m x 10m. Data on the number of eggs and juveniles were subjected to analysis of variance and the comparison of the average of eggs and juveniles per treatment was obtained by the Skott-knot test at 5% probability and soybean productivity was calculated. At 32 and 60 days after emergence, treatment with P. lilacinum provided the lowest rates of nematodes in the roots and soil. The highest productivity occurred in the treatment with Ecotrich®. The lowest productivity was observed in the treatment with Avicta®+Nemat®+Ecotrich®. The combination of Nemat® with Avicta®+Cruiser®+Maxim XL® and with Avicta®+Cruiser®+Maxim®+Ecotrich®, provided lower productivity. The highest productivity occurred in the Nemat®+Ecotrich® treatment. Sequential application, during two seasons of Ecotrich® alone and Nemat®+Ecotrich®, reduced the populations of P. brachyurus.